Antiobesity efficacy of GLP‐1 receptor agonist liraglutide is associated with peripheral tissue‐specific modulation of lipid metabolic regulators. (23rd May 2016) - Decara, Juan; Arrabal, Sergio; Beiroa, Daniel; Rivera, Patricia; Vargas, Antonio; Serrano, Antonia; Pavón, Francisco Javier; Ballesteros, Joan; Dieguez, Carlos; Nogueiras, Rubén; Rodríguez de Fonseca, Fernando; Suárez, Juan
Abstract: To investigate the role of glucagon‐like‐peptide‐1 receptor (GLP‐1R) in peripheral lipid metabolism. Both lean and high‐fat diet (HFD)‐induced obesity (DIO) rats were used to compare the peripheral effects of the subcutaneous and repeated administration of the GLP‐1R agonist liraglutide on the expression of key regulators involved in lipid metabolism, β‐oxidation and thermogenesis in liver, abdominal muscle, and epididymal white adipose tissue (eWAT). We observed that liraglutide reduced caloric intake, body weight, and plasma levels of triglycerides and VLDL in a diet‐independent manner. However, changes in liver fat content and the expression of lipid metabolism regulators were produced in a diet and tissue‐dependent manner. In lean rats, liraglutide increased the gene/protein expression of elements involved in lipogenesis ( ChREBP, Acaca /ACC, Fasn /FAS, Scd1 /SCD1, PPARα/γ), β‐oxidation (CPT1b), and thermogenesis ( Cox4i1, Ucp1 /UCP1) in eWAT and muscle, which suggest an increase in fatty‐acid flux and utilization to activate energy expenditure. Regarding DIO rats, the specific reduction of liver lipid content by liraglutide was associated with a decreased expression of main elements involved in lipogenesis (phospho‐ACC), peroxisomal β‐oxidation (ACOX1), and lipid flux/storage ( Pparγ /PPARγ) in liver, which suggest a recovery of lipid homeostasis. Interestingly, the muscle of DIO rats treated with liraglutide showed a decreased expression of PPARγ and the thermogenic factor UCP1. These results help us to better understand the peripheral mechanisms regulating lipid metabolism that underlay the effectiveness of GLP‐1 analogues for the treatment of diabetes and obesity. © 2016 BioFactors, 42(6):600–611, 2016